2022
DOI: 10.3389/fpubh.2022.829362
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Activity in the Daytime, but Not the Nighttime, Predicts Better Mental Health Status During the COVID-19 Curfew in the United Arab Emirates

Abstract: BackgroundThe COVID-19 pandemic and the associated infection prevention and control measures had a negative impact on the mental health of many people. In the United Arab Emirates (UAE), infection control measures implemented after March 24th, 2020, placed necessary restrictions on people's freedom of movement.AimThis study aimed to assess the association between levels of daytime vs. nighttime outdoor activity and mental health among a sample of UAE residents during the lockdown period.MethodAn opportunity sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…This program was conducted from 10 a.m. to 12 a.m., and it is thought that the depression symptoms of patients improved because it led them to be naturally exposed to sunlight through various forest activities such as stretching, walking, and emotional cards. For example, Anouti et al [91] conducted an online survey of 245 participants evaluating depression, physical symptoms, and levels of day and night activity. Multivariate logistic regression analysis showed that only daytime outdoor activities, not night outdoor activities, were associated with a clinically significant reduction in the risk of depression and physical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This program was conducted from 10 a.m. to 12 a.m., and it is thought that the depression symptoms of patients improved because it led them to be naturally exposed to sunlight through various forest activities such as stretching, walking, and emotional cards. For example, Anouti et al [91] conducted an online survey of 245 participants evaluating depression, physical symptoms, and levels of day and night activity. Multivariate logistic regression analysis showed that only daytime outdoor activities, not night outdoor activities, were associated with a clinically significant reduction in the risk of depression and physical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, in Jordan, Lebanon, Syria and Afghanistan, the cutoff point of 10 was used [ 24 27 ]. Similarly, in the UAE, studies have mostly used the cutoff point of 10 [ 28 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a representative survey, the study found a strong correlation between changes in outdoor activity and changes in subjective well-being [ 9 ]. Al-Anouti et al conducted an online survey of 245 participants to assess the relationship between residents’ daytime and nighttime outdoor activity levels and mental health during the COVID-19 pandemic; the link between nighttime and better mental health may be attributable to vitamin D, but more in-depth research was needed to confirm it [ 10 ]. Outdoor play increases the risk of contracting or spreading the coronavirus.…”
Section: Introductionmentioning
confidence: 99%